AI-Driven Business Intelligence and Financial Data Visualization: Transforming Modern Analytics - Mallikarjun Reddy Ramasani, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The convergence of Artificial Intelligence (AI) with Business Intelligence (BI) and Financial Data Visualization has fundamentally transformed how financial institutions approach data analysis and decision-making. This comprehensive article examines the evolution and impact of AI-driven technologies in financial services, focusing on advanced analytics, visualization techniques, and automated decision support systems. It explores how machine learning, deep learning, and natural language processing capabilities have enhanced financial institutions' ability to process complex data sets, detect patterns, and generate actionable insights. The article investigates the implementation frameworks necessary for successful AI integration, including technical architecture requirements and governance best practices. It further analyzes emerging trends and challenges in AI-driven financial operations, particularly in areas of risk assessment, regulatory compliance, and customer service. By examining both current applications and future directions, this article provides valuable insights into how AI-powered solutions are reshaping the financial sector's approach to data visualization and analysis while highlighting the importance of balanced implementation strategies that consider both technological capabilities and practical business needs.
Keywords: Artificial Intelligence in Finance; Business Intelligence Analytics; Financial Data Visualization; Machine Learning Applications; AI Governance Framework